EVALUASI BOBOT BIJI TIAP JENIS MALAI ANAKAN PADI MELALUI PENERAPAN ANALISIS PROFIL PEUBAH GANDA - Sutoro, Sutoro (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2015)
Yield components of rice are characteristics that can contribute to crop productivity levels. Grain weight per panicle produced from primary, secondary, tertiary and quarter tiller are important yield components. Information on grain weight profile may be used as the basis for improving rice cultivation techniques. Therefore, profile of the filled and empty grain weight from each type of rice panicle need to be evaluated. Evaluation of the traits was done by conducting experiment in glass house in 2013 under randomized block design, 3 replications with 1 plant per pot. Seed weight of filled and empty grain of primary, secondary, tertiary and quarter of rice panicles were observed. Thirty genotypes of rice were grouped by 8 variables of filled and empty grain weight through cluster analysis, and the profile response of filled and empty grain weight was analyzed by profile analysis of multiple variables. Profile of grain weight per cluster showed that there was no cluster with high filled grain weight and low empty grain weight for all types of panicle. Among the clusters, there were genotypes with high filled grain weight and moderate empty grain weight from each type of panicles, and they could be considered as materials in rice breeding programs.